Reconsidering Polygamy Law Through The Lens Of Substantive Justice: A Critical Analysis Of Islamic Family Law In Indonesia - Adang Djumhur Salikin (Jurnal Legisci, 2026)
Background. The urgency of this research lies in the persistent gap between normative legal provisions and the lived experiences of justice among women in polygamous marriages, as evidenced by mounting empirical data on economic disenfranchisement, psychological distress, and social stigmatization. Aims. This article aims to critically examine polygamy law in Indonesia not merely from a legal-formal perspective but through the lens of substantive justice. It seeks to answer whether polygamy regulations (Marriage Law No. 1/1974 and the Compilation of Islamic Law) have produced tangible justice for all affected parties, particularly women and children, or merely serve as administrative procedures that legitimize patriarchal practices. Methods. This research employs normative legal research with philosophical, statutory, and comparative approaches. The analysis draws upon substantive justice theories from critical legal studies and legal philosophy—particularly Gustav Radbruch's triadic theory of law (justice, certainty, utility), Satjipto Rahardjo's Progressive Law, and Asghar Ali Engineer's theory of substantive justice for the weak—as analytical tools to examine polygamy provisions and their implementation in Religious Courts. Result. This research reveals a fundamental disparity between legal texts and the reality of justice. First, polygamy regulations (Articles 4 and 5 of Marriage Law No. 1/1974) remain highly procedural and have not addressed psychological and social justice dimensions for wives and children. The requirement of "justice" is only proven through written statements and the first wife's consent, without any mechanism to verify the husband's psychological capacity to be just. Second, judicial practice tends to be formalistic—if administrative requirements (wife's consent letter, income statement, police certificate) are fulfilled, applications are granted without a deeper examination of substantive justice. Conclusion. The article integrates multiple theoretical frameworks: substantive justice theory, maqashid shariah, feminist jurisprudence, and comparative legal analysis. It provides concrete reform recommendations based on empirical evidence and successful models from other Muslim-majority countries, offering a blueprint for legal reform that balances religious validity with enforceable safeguards. The article also introduces the concept of "Legal System Ibuism" as a novel analytical framework for understanding systemic gender bias in Indonesian marriage law.